2007
DOI: 10.1093/brain/awm064
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ventrolateral frontal cortex in inhibitory oculomotor control

Abstract: It has been proposed that the inferior/ventrolateral frontal cortex plays a critical role in the inhibitory control of action during cognitive tasks. However, the contribution of this region to the control of eye movements has not been clearly established. Here, we describe the performance of a group of 23 frontal lobe damaged patients in an oculomotor rule switching task for which the association between a centrally presented visual cue and the direction of a saccade could change from trial to trial. A subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
61
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 55 publications
(63 reference statements)
11
61
0
Order By: Relevance
“…The similarity between this finding and previous results using an infrared eye tracker, [11][12][13]33 along with the strong correlation of performance on the BAS and our laboratory AS task, further underscores the validity of the task. Impaired AS performance is correlated with structural alterations to the right greater than left premotor regions of the frontal lobes in focal lesion patients, 34 neurodegenerative disease, 12 psychiatric illness, 35 and normal aging. 4,36 Our results suggest that the BAS may be sensitive to damage to these same brain regions and could be used as a screen for such damage at the bedside.…”
Section: Resultsmentioning
confidence: 98%
“…The similarity between this finding and previous results using an infrared eye tracker, [11][12][13]33 along with the strong correlation of performance on the BAS and our laboratory AS task, further underscores the validity of the task. Impaired AS performance is correlated with structural alterations to the right greater than left premotor regions of the frontal lobes in focal lesion patients, 34 neurodegenerative disease, 12 psychiatric illness, 35 and normal aging. 4,36 Our results suggest that the BAS may be sensitive to damage to these same brain regions and could be used as a screen for such damage at the bedside.…”
Section: Resultsmentioning
confidence: 98%
“…Importantly, the network described above may be effector independent, because preSMA, IFC, and the STN are also recruited by NoGo or stopping studies that have examined the control of eye movements (Stuphorn and Schall, 2006;Chikazoe et al, 2007;Hodgson et al, 2007;Isoda and Hikosaka, 2007a,b) and speech (Xue et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Further, a recent lesion study in humans has shown that the rFIC has an important role in cognitive control related to task switching. Using an oculomotorswitching task Hodgson and colleagues (45) showed that patients with lesions in the anterior rFIC were the most impaired in altering their behavior in accordance with the changing rules of the task. In normal healthy adults, functional brain imaging studies have suggested that the FIC and the ACC are together involved in a variety of cognitive control processes, including conflict and error monitoring, interference resolution, and response selection (23,36,40,(46)(47)(48).…”
Section: Differential Roles Of the Rfic Acc And Lateral Prefrontal mentioning
confidence: 99%